Risk Evaluation of Endocrine-Disrupting Chemicals - Laura Gioiosa; Paola Palanza; Stefano Parmigiani; Frederick S. vom Saal (SAGE Publishing, 2015)
We review here our studies on early exposure to low doses of the estrogenic endocrine-disrupting chemical bisphenol A (BPA) on behavior and metabolism in CD-1 mice. Mice were exposed in utero from gestation day (GD) 11 to delivery (prenatal exposure) or via maternal milk from birth to postnatal day 7 (postnatal exposure) to 10 µg/kg body weight/d of BPA or no BPA (controls). Bisphenol A exposure resulted in long-term disruption of sexually dimorphic behaviors. Females exposed to BPA pre- and postnatally showed increased anxiety and behavioral profiles similar to control males. We also evaluated metabolic effects in prenatally exposed adult male offspring of dams fed (from GD 9 to 18) with BPA at doses ranging from 5 to 50 000 µg/kg/d. The males showed an age-related significant change in a number of metabolic indexes ranging from food intake to glucose regulation at BPA doses below the no observed adverse effect level (5000 µg/kg/d). Consistent with prior findings, low but not high BPA doses produced significant effects for many outcomes. These findings provide further evidence of the potential risks that developmental exposure to low doses of the endocrine disrupter BPA may pose to human health, with fetuses and infants being highly vulnerable.